2013
DOI: 10.5935/1678-9741.20130050
|View full text |Cite
|
Sign up to set email alerts
|

The descending branch of the lateral femoral circumflex artery is a good option in CABG with arterial grafts

Abstract: Rev Bras Cir Cardiovasc | Braz J Cardiovasc SurgRev Bras Cir Cardiovasc 2013;28(3):317-24 Gaiotto FA, et al. -The descending branch of the lateral femoral circumflex artery is a good option in CABG with arterial grafts RBCCV 44205-1476 DOI: 10.5935/1678 The descending branch of the lateral femoral circumflex artery is a good option in CABG with arterial grafts Ramo descendente da artéria circunflexa lateral femoral é boa opção para revascularização do miocárdio com enxertos arteriais ORIGINAL ARTICLE Abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Interestingly, the experience of Sakakibara et al () suggested that larger caliber DBLCFAs could be of greater importance as collateral channels and therefore should be rather saved and not harvested. Moreover, Gaiotto et al () found a high patency rate and positive luminal adaptation when they used the DBLCFA in 32 patients with CABG, but owing to a high incidence of anatomical variations they suggested that preoperative femoral angiographic examination was mandatory. However, this would be difficult in patients suffering from overall atherosclerosis, which often entails deterioration of kidney function, and patients with severe kidney problems may be unsuited for CTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the experience of Sakakibara et al () suggested that larger caliber DBLCFAs could be of greater importance as collateral channels and therefore should be rather saved and not harvested. Moreover, Gaiotto et al () found a high patency rate and positive luminal adaptation when they used the DBLCFA in 32 patients with CABG, but owing to a high incidence of anatomical variations they suggested that preoperative femoral angiographic examination was mandatory. However, this would be difficult in patients suffering from overall atherosclerosis, which often entails deterioration of kidney function, and patients with severe kidney problems may be unsuited for CTA.…”
Section: Discussionmentioning
confidence: 99%
“…The DBLCFA is not universally usable as it was not available in 27% of the patients and requires CTA beforehand. The graft might be inappropriate for use in a high percentage of patients (19%) owing to anatomical variations such as short length, narrow lumen diameter, and silent atherosclerosis (Gaiotto et al, ). Another drawback is that the DBLCFA is a muscular limb artery classified as more prone to vasospasm because of its greater sensitivity to circulating catecholamines and other vasoconstrictors than more elastic conduits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative anatomical assessment of LCFA through arteriographic study is also essential. The LCFA is frequently explored for its use as new arterial graft for coronary artery bypass grafting [12] . During such surgical procedures, an atypical course of LCFA may lead to an unfortunate sequel of injury to branches of femoral nerve traversing in front of LCFA.…”
Section: Discussionmentioning
confidence: 99%
“…The branches of PFA are also used as long vascular pedicle during breast reconstruction after mastectomy in cases of carcinoma of breast. [7,8,9] Bergman et al describe that various vessel of the profunda complex may more or less dissociate, one or another of them having an independent origin from the femoral artery; this may occur to such an extent that a profunda femoris as a definite vessel may not exist. Differing patterns of the origin of the PFA and its branches have been described on a racial basis as well as variations being noted between the two legs of the same individual.…”
Section: Introductionmentioning
confidence: 99%